EFFECTS OF PHYSICAL EXERCISE FOR ADULTS WITH INTELLECTUAL DISABILITIES: A SYSTEMATIC REVIEW - Pestana, Mayara Borkowske; Barbieri, Fabio Augusto; Vitório, Rodrigo; Figueiredo, Gabriella Andreeta; Mauerberg-decastro, Eliane (Universidade Estadual de Maringá, 2018)
ABSTRACT The literature presents the benefits of physical activity programs for people with intellectual disabilities (ID), but aspects such as those related to physical exercise prescription, benefits of the type of exercise program, the most recommended exercises, load control, and limitations of the interventions for adults with ID are subjects awaiting scientific research. The aim of this study was to verify, through a systematic review, the effects of physical activity programs for adults with ID. The procedure included an electronic search of the literature published from January 1960 to August 2014, considering terms related to physical activity, ID, and physical activity programs. Eight manuscripts met the eligibility criteria and were included in the study. Based on the systematic review, we found a limited number of studies that investigated, in a structured way, the effect of physical activity programs for adults with ID. In general, the systematized programs of physical exercise promoted consistent and significant benefits for adults with ID. However, there seems to be no consensus on the type of intervention to be used to promote the practice of physical activity in adults with ID. In addition, the methodological quality of the studies appears to be limited. We conclude that intervention studies with physical activity in adults with ID that involve aerobic exercise, sports specialization, and a combination of muscular and aerobic exercise performed two or three times a week for more than 40 minutes seem to be the most highly recommended for adults with ID.

RESUMO Apesar da literatura apresentar os benefícios de programas de atividade física para a pessoa com deficiência intelectual (DI), aspectos como os relacionados à prescrição de exercício físico, benefícios de cada tipo de programa de exercício físico, exercícios mais recomendados, controle de carga, limitações das intervenções para adultos com DI são assuntos em espera de investigação científica. O objetivo deste estudo foi verificar, por meio de uma revisão sistemática, quais os efeitos de programas de atividade física para adultos com DI. O procedimento incluiu uma busca eletrônica da literatura publicada de janeiro de 1960 até agosto de 2014, considerando termos relacionados à atividade física, DI e programa de atividade física. Oito manuscritos preencheram os critérios da elegibilidade e foram incluídos no estudo. Com base na revisão sistemática, foi encontrado um limitado número de estudos que investigou, de forma estruturada, o efeito de programas de atividade física para adultos com DI. De forma geral, os programas sistematizados de exercício físico promoveram benefícios consistentes e significantes para adultos com DI. Entretanto, parece não haver um consenso do tipo de intervenção a ser utilizada para promover a prática de atividade física de adultos com DI. Além disso, a qualidade metodológica dos estudos parece ser limitada. Concluímos que estudos de intervenção com atividade física em adultos com DI que envolvem exercícios aeróbios, especialização esportiva e combinação de exercício de força muscular e aeróbio realizadas duas ou três vezes por semana por mais de 40 minutos parecem ser os mais recomendados para adultos com DI.
EFEITOS DO EXERCÍCIO FÍSICO PARA ADULTOS COM DEFICIÊNCIA INTELECTUAL: UMA REVISÃO SISTEMÁTICA
Keywords: Intellectual Disability; Exercise; Quality of life.; Deficiência intelectual; Exercício; Qualidade de vida.